Knowledge and Behavior of Health Workers on Antibiotic Stewardship at Private Hospital in Pontianak - Putri, Lidya Hafidzah; IH, Hariyanto; Mardhia, Mardhia; Liana, Delima Fajar; Mahyarudin, Mahyarudin (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: One of the causes of increasing antimicrobial resistance is health workers' lack of knowledge about antibiotics, thus causing irrational behavior in antibiotic stewardship.Objectives: This study aimed to analyze the knowledge and behavior among health workers about antibiotic stewardship and their relationship at a private hospital in Pontianak.Methods: This study was a descriptive observational study with a cross-sectional design. Data were collected using consecutive sampling of health workers involved in antibiotic prescribing using a validated and reliable questionnaire. The data were analyzed using Spearman Rank correlation to determine the relationship between knowledge level and behavior.Results: 39 respondents participated, including nine general doctors, 17 specialists, and 13 pharmacists. Most health workers were 26–35 years old (43.59%) and had worked for 1–5 years (48.72%). All respondents had a good knowledge (100%) of the knowledge topic of the etiology, control, and effect of antibiotic resistance. However, only 76.92% of respondents had good behavior, and the rest had moderate behavior (23.08%) on the behavioral topics in the performance of antimicrobial resistance control programs, controlling antibiotic prescribing, performance preventing the spread of resistant microbes, and good antibiotic prescribing practice. The knowledge had a significant relationship towards behavior (p<0.05) with a correlation coefficient (r)=0.568.Conclusion: Most health workers in a private hospital had good knowledge and behavior about antibiotic stewardship, and there was a moderately strong and positive relationship between them.